Epidemiology and clinical characteristics of hospitalized elderly patients for heart failure with reduced, mid-range and preserved ejection fraction - Gök, Gülay; Kılıç, Salih; Sinan, Ümit Yaşar; Türkoğlu, Ebru; Kemal, Hatice; Zoghi, Mehdi (Mosby-Elsevier, 2020)
Introduction: Elderly patients hospitalized with heart failure (HF) have high mortality rates and require& specific evidence based theraphy, however there are few studies which have focused on patients older than 80 years hospitalized with HF. The aim of the present study is to evaluate the overall clinical characteristics, management, and in-hospital outcomes of elderly patients hospitalized with HF.Methods: Journey-HF study was conducted in 37 different centers in Turkey and recruited 1606 patients who were hospitalized with HF between September 2015 and September 2016. In this study, clinical profile of patients >= 80 years old and 65-79 years old hospitalized with HF were described and compared based on EF-related classification: HFrEF (HF with reduced ejection fraction), HFmrEF (HF with mid-range ejection fraction) and HFpEF (HF with preserved ejection fraction).Results: A total of 1034 elder patients (71.6% 65-79 years old and 28.4% >= 80 years old) were recruited. Of the 65-79 years old patients 67.4% had HFrEF, 16.2% had HFmrEF and 16.3% had HFpEF. Among patients >= 80 years old 61.6% had HFrEF, 15.6% had HmrEF and 22.8% had HFpEF.When compared with patients with HFrEF and HFmrEF, patients >80 years old with HFpEF were more likely to be older, have atrial fibrilation (AF), and less likely to have diabetes mellitus (DM), coronary artery disease (CAD) or to be recieving an angiotensin-converting enzyme inhibitor (ACEi) or beta blocker theraphy. When compared to patients 65-79 years old with HFpEF, patients >= 80 years with HFpEF had a higher rate of AF and less likely DM. Acute coronary syndrome was the most common precipitant factor for hospitalization in both age groups with HFrEF group. Arrhythmia was a major precipitant factor for hospitalization of patients >= 80 years old with HFpEF. Non-compliance with theraphy was a major problem of patients >= 80 years old with HFrEF.Conclusion: Elderly patients with HFrEF, HFmrEF and HFpEF each had characterized unique patient profiles and the guideline recommended medications were less likely to be used in these patient populations. In hospital mortality rate is worrisome and reflects a need for more specific tretment strategy.
Keywords: Heart Failure; Elder Patients; Epidemiology